2018
DOI: 10.1021/acs.biochem.8b00607
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Methotrexate Conjugates by Folate Receptor-α

Abstract: The folate antagonist methotrexate is a cytotoxic drug used in the treatment of several cancer types. The entry of methotrexate into the cell is mediated by two main transport systems: the reduced folate carrier and membraneassociated folate receptors. These transporters differ considerably in their mechanism of (anti)folate uptake, substrate specificity, and tissue specificity. Although the mechanism of action of the reduced folate carrier is fairly well-established, that of the folate receptor has remained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Intestinal tissue adsorption of MTX occurs by the proton-coupled folate transporters (PCFTs), which are a solute carrier transporter, while a cellular drug penetration is followed mainly by the reduced folate carrier 1 (RFC1), an APT-binding cassette transporter. To a small extent, MTX also uses receptor-mediated endocytosis via folate receptors (FRs), the glycosyl-phosphatidyl-inositol (GPI)-anchored membrane proteins that may internalize bound folates and folate conjugates [32,33]. Intracellularly, MTX is metabolized by folylpolyglutamyl synthase (FPGS) to a polyglutamate derivatives (MTX Glu ), that show significantly increased cell residence time and bioactivity in comparison to initial MTX form ( Figure 2) [34][35][36].…”
Section: Methotrexate-mechanisms Of Drug Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal tissue adsorption of MTX occurs by the proton-coupled folate transporters (PCFTs), which are a solute carrier transporter, while a cellular drug penetration is followed mainly by the reduced folate carrier 1 (RFC1), an APT-binding cassette transporter. To a small extent, MTX also uses receptor-mediated endocytosis via folate receptors (FRs), the glycosyl-phosphatidyl-inositol (GPI)-anchored membrane proteins that may internalize bound folates and folate conjugates [32,33]. Intracellularly, MTX is metabolized by folylpolyglutamyl synthase (FPGS) to a polyglutamate derivatives (MTX Glu ), that show significantly increased cell residence time and bioactivity in comparison to initial MTX form ( Figure 2) [34][35][36].…”
Section: Methotrexate-mechanisms Of Drug Actionmentioning
confidence: 99%
“…The action leading to a local increase of the adenosine concentration at the site of inflammation and also the specific immunosuppressive effect of MTX play an important role in the treatment of severe inflammation and autoimmune diseases (arthritis, psoriasis, myasthenia gravis). Moreover, MTX may serve as vector leading the MTX-attached agents to specific molecular targets like RFC or, less likely FRs [32,33,62,63], to be overexpressed on various cancer cells. While FA plays the role of a Trojan horse for molecular selective delivery of the FA-attached agent to FR-expressing cancer cells, MTX is considered the cornerstone of anti-folate therapy in the treatment of several malignancies.…”
Section: Methotrexate-applications In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…20 The recent findings of Nogueira et al; regarding the conjugation pattern of MTX molecule demonstrated that the carboxylic terminal of MTX molecule engaged in conjugation, leaving amino-terminal free for receptor binding; as a result, the internalization of MTX-conjugates to epithelial cancer cell through FAα is accelerated. 21 Once the targeted nanoparticles internalized through endocytosis, the conjugated drug molecules were released from nanoparticles inside the cell due to the acidic pH of the lysosome. The released MTX inhibits nucleotide biosynthesis by irreversibly binding with the key enzymes of the synthesis pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent MTX was shown to bind FRα 56. Recent studies showed that the amino groups of MTX play a key role in targeting FRα 57. Most recently, studies have found that G5-PAMAM-FA-MTX has a stronger FRβ targeting effect compared to G5-PAMAM-FA 42.…”
Section: Introductionmentioning
confidence: 99%